Membangkitkan Kembali Kelaparan Akan Kebenaran Firman Tuhan Dalam Konteks Masa Kini (Amos 8:11-14) - Tupa Pebrianti Sihombing; Helma Mesya Cristiani Br Siregar (International Forum of Researchers and Lecturers, 2024)
This study explores the theme of rekindling the hunger for the truth of God's word in contemporary contexts, drawing from the prophecy of Amos 8:11-14. The passage highlights a period when people will experience a profound spiritual famine, not of physical sustenance, but of hearing the words of the Lord. Historically, this famine signified a divine judgment on the people of Israel for their moral and spiritual deviations despite their material prosperity. In today's context, this spiritual hunger remains relevant as modern society grapples with materialism, technological advancements, and a subsequent spiritual void. Many individuals seek meaning and direction but often fail to find lasting fulfillment. This paper emphasizes the enduring need for God's word as a source of truth, guidance, and comfort. Key aspects include, Spiritual Hunger The persistent spiritual emptiness experienced by many, underscoring the necessity of God's word for true satisfaction. Role of the Church,The importance of churches and Christian communities in teaching and disseminating God's word effectively to meet contemporary spiritual needs. Utilizing Media and Technology, Leveraging digital platforms to spread biblical teachings and reach a broader audience in the digital age. Individual Responsibility, Encouraging personal engagement with Scripture to foster a deeper relationship with God and to serve as living testimonies to others. The study concludes that rekindling the hunger for God's word is crucial in addressing the spiritual needs of today's society, offering a timeless guide and a source of hope for those seeking truth. This calls for a collective effort by individuals and faith communities to prioritize and propagate the transformative power of God's word in a world often devoid of spiritual direction.